Amendoim inoculado com rizóbio e coinoculado com Azospirillum brasilense em solo com e sem compactação - Neves, Laura Cristina Rezende das (2018)
Peanut is a legume rich in oil, vitamins, proteins, minerals, and is used for various purposes. Studies for this crop are important to verify the degree of adaptation and the productive capacity of the peanut when subjected to some stress, such as compaction. Compaction causes a number of problems, such as hinders the absorption of water and nutrients by plants. An alternative to minimize the impacts of this process is the use of nitrogen-fixing microorganisms and plant growth promoters, with the purpose of evaluating whether isolated or combined inoculation could bring beneficial effects to peanuts in compacted soil. The objective of this study was to verify the effect of inoculation with rhizobia and the co-inoculation with Azospirillum brasilense on peanut cultivated in Cerrado Oxisol with and without compaction. The experiment was conducted in a greenhouse in a randomized block design in a 5x2 factorial scheme, with 4 replications, totaling 40 vessels. The treatments were composed of commercial peanut inoculant (Bradyrhizobium elkanii, strain SEMIA 6144); strain MT 15 (Rhizobium tropici); MT 15 + commercial inoculant with A. brasilense; nitrogen control and absolute control (without NPK and micronutrients and without inoculation) in soil with and without compaction. The variables analyzed were plant height, leaf number, number of branches per plant, stem diameter, Falker chlorophyll index, shoot dry weight, root dry matter per layer and total dry mass, dry mass ratio aerial part by root dry matter, root volume per layer and total, number and dry mass of nodules per layer and total, number of pods, number of grains, dry mass of the grains, nitrogen concentration in shoot and in the grains, crude protein and accumulation of nitrogen in the aerial part and in the grains. The data were submitted to analysis of variance and when significant to the Tukey test up to 5% of probability by means of the SISVAR Statistical Program. The inoculation with the MT15 strain and the co-inoculation with A. brasilense provided the peanut crop with good performance in relation to the phytometric characteristics, productive and related to the biological nitrogen fixation efficiency in compacted and uncompacted soil.